CHEMICAL QUALITY CHARACTERISTICS OF TEHRAN GROUND WATER - K. Imandel; V. Iranshahi (Tehran University of Medical Sciences, 1994)
For better understanding of Tehran ground water, samples were taken randomly from 340 out of 655 deep & semi deep wells in 1993, which dug by Tehran Water Supply and Sewage Engineering Company. 260 Water specimens were examined chemically and physically and compared with the 1993 World Health Organization (WHO) and Food and Agriculture Organization (FAO) criteria and analyzed statistically. Logarithmic diagram of arithmetic mean of 53 deep wells which are now connected to Tehran water supply system showed Sodium- Sulphate category. Main chemical components of water are closely adjusted to the international standards and no overdoses were observed in any cases. Logarithmic diagram of arithmetic mean of 72 deep wells, which were rsed for the Tehran's orbital town's drinking water, showed that chemical components of the water were Calcic-Chloride category and there were not observed any increases within the other compounds.